Choice Criteria of Cosmetics among Chinese Consumers - LI, ZHU (2014)
Becoming familiar with consumers’ choice criteria towards a certain kind of product can help marketers tailor more efficient market strategies. Cosmetics play a very important part in the lives of women. Plautus asserted, “A woman without paint is like food without salt”. In recent years, the Chinese cosmetic market has flourished. The aim of this dissertation is to understand the choice criteria of cosmetics in the context of the Chinese market. Country-of-origin, brand image and quality are the three choice criteria that will be focused upon. In order to achieve this aim, a qualitative research method is adopted and data will be collected employing semi-structured in-depth interview. Twelve young Chinese females are enlisted as respondents. It is found that among the aforementioned choice criteria, brand image and quality significantly influence Chinese consumers’ evaluation of cosmetics. In contrast, Chinese consumers do not pay much attention to or actively seek out a particular country-of-origin when purchasing cosmetic products. However, if they are presented with country-of-origin information in relation to a cosmetic product, the brand image of this cosmetic product in their own minds and their perception of product quality will be influenced by country-of-origin information, even if this occurs unconsciously. This dissertation aids marketers in achieving a better understanding regarding consumer priorities when evaluating cosmetics, so market resources can be allocated more efficiently.